DROP HEIGHT IS INFLUENCED BY BOX HEIGHT BUT NOT BY INDIVIDUAL STATURE DURING DROP JUMPS - Gislaine de Fátima Geraldo; Sarah da Glória Teles Bredt; Hans-Joachim Karl Menzel; Gustavo Henrique da Cunha Peixoto Cançado; Lucas Abreu Carneiro Mitraud Carvalho; Fernando Vitor Lima; Jéssica da Silva Soares; André Gustavo Pereira de Andrade (Journal of Physical Education)
ABSTRACT Drop jump (DJ) performance an important aspect in many sports. The optimal stretch load in the DJ training is commonly prescribed through the box height from which individuals must drop from. However, studies have reported differences between real (calculated) drop heights and box heights, which may affect the quality of the prescription of DJ training load. Other aspects such as individual stature may also affect the differences between calculated drop heights and box heights. This study aimed to 1) investigate the difference between calculated drop heights and box heights in different box heights and 2) verify the influence of individual stature on the difference between calculated drop heights and box heights. Twenty-two individuals performed DJs from different box heights and landed on a force platform. An ANCOVA was performed to verify the influence of stature and box height on the difference between calculated drop heights and box heights. We found that calculated drop height was different from box height for all box heigths. The difference between calculated drop height and box height significantly increased as box heights increased. Individual stature did not influence the difference between calculated drop heights and box heights. We can concluded that box heights are significantly different from calculated drop heights. These differences increase as the box height increases, i.e. an increase in the difference of approximately 2 cm every 10 cm increase in box height. Therefore, it seems that coaches can use the same procedures for prescribing DJ training load for individuals of different heights